Trichoderma spp. promotes ginseng biomass by influencing the soil microbial community - Zhang, Linlin; Jin, Qiao; Guan, Yiming; Liu, Zhengbo; Pan, Xiaoxi; Zhang, Yue; Zhang, Yayu; Wang, Qiuxia (Frontiers in Microbiology, 2024)
Introduction Ginseng (Panax ginseng C.A. Meyer) has multiple effects on human health; however, soil degradation seriously affects its yield. Trichoderma spp. play an important role in improving plant biomass by influencing the soil environment. Therefore, it is necessary to screen efficient Trichoderma strains that can increase ginseng biomass and determine their mechanisms. Methods Herein, we selected six Trichoderma species (T. brevicompactum, T. velutinum, T. viridescens, T. atroviride, T. koningiopsis, and T. saturnisporum) isolated from ginseng rhizosphere soil, and evaluated their growth promoting effects on ginseng and their influence on the microbiome and chemical attributes of the ginseng rhizosphere soil. Results Except for T. saturnisporum (F), compared with the control, the other five species increased ginseng biomass. In terms of chemical properties, the pH value, available potassium content, and available phosphorus content in the ginseng rhizosphere soil increased by 1.16-5.85%, 0.16-14.03%, and 3.92-38.64%, respectively, after root irrigation with spores of Trichoderma species. For the soil microbiome, fungal Chao1 and Ace richness indices decreased.Application of Trichoderma enhanced the relative level of Proteobacteria, but reduced the relative level of Ascomycota. At the genus level, application of Trichoderma enhanced the relative levels of Sphingomonas, Blastomonas, and Trichoderma, but reduced the relative level of Fusarium. Available K and available P were the most important elements that affected the structure of the bacterial community, while total K was the most influential element for the structure of the fungal community structure.The results indicated that the application of Trichoderma spp. could increase soil nutrients and regulate the structure and composition of the soil microbial community, thereby enhancing the biomass of ginseng. The results will provide guidance for soil improvement in ginseng cultivation.